Analisis Perubahan Biaya Terhadap Perolehan Laba Industri Moulding dengan Menggunakan Pendekatan Biaya-Kapasitas-Laba pada PT Sako Indah Gemilang Palembang - Zikri, Filani (Jurnal Ilmiah Kesatuan (JIK), 2000)
This study is aimed at analyzing change of costs, in order to produce moulding, and its effect to the profit using cost-capacity-profit approach. This tool is chosen since it can be used to examine the relationship between cost, including fix and variable cost, production capacity, and profitability. From the discussion it was suggested that company management need to concern to cost efficiency in order to get higher benefits, since the moulding industry is still profitable. Keywords: Analisis Perubahan Biaya; Industri Moulding; Biaya-Kapasitas-Laba